Acceptability and feasibility of a mobile phone-based case management intervention to retain mothers and infants from an Option B+ program in postpartum HIV care - SCHWARTZ, Sheree R (Matern Child Health J, 2015)
OBJECTIVE: To assess the acceptability and feasibility of a cell-phone based case manager intervention targeting HIV-infected pregnant women on highly-active antiretroviral therapy (HAART). METHODS: Pregnant women ≥36 weeks gestation attending antenatal care and receiving HAART through the Option B+ program at a primary care clinic in South Africa were enrolled into a prospective pilot intervention to receive text messages and telephone calls from a case manager through six weeks postpartum. Acceptability and feasibility of the intervention were assessed along with infant HIV testing rates and 10-week and 12-month postpartum maternal retention in care. Retention outcomes were compared to women of similar eligibility receiving care prior to the intervention. RESULTS: Fifty women were enrolled into the pilot from May-July 2013. Most (70%) were HAART-naive at time of conception and started HAART during antenatal care. During the intervention, the case manager sent 482 text messages and completed 202 telephone calls, for a median of 10 text messages and 4 calls/woman. Ninety-six percent completed the postpartum interview and 47/48 (98%) endorsed the utility of the intervention. Engagement in 10-week postpartum maternal HIV care was >90% in the pre-intervention (n=50) and intervention (n=50) periods; by 12-months retention fell to 72% and was the same across periods. More infants received HIV-testing by 10-weeks in the intervention period as compared to pre-intervention (90.0% vs. 63.3%, p<0.01). CONCLUSIONS: Maternal support through a cell-phone based case manager approach was highly acceptable among South African HIV infected women on HAART and feasible, warranting further assessment of effectiveness.